Doing more with less: New markers for sarcoma diagnosis and their applicability to cytology specimens. Issue 4 (18th January 2016) - Dodd, Leslie G; Ware, Patrick; Duncan, Daniel; Hertel, Johann
Abstract : Sarcomas are a rare and extremely diverse set of neoplasms that are often a challenge to diagnose for pathologists. For a number of reasons, primary diagnosis of soft tissue neoplasms is increasingly being performed on small biopsy specimens including fine needle aspiration (FNA) and core needle biopsy (CNB). In the last several years, there has been a significant increase in our understanding of the molecular pathogenesis of this group of tumors. New insights into the genetic mechanisms of tumor formation have been exploited to create a new generation of diagnostic markers that are accessible to most laboratories. This review describes a number of new ancillary markers, and how they can facilitate accurate diagnosis of soft tissue neoplasms on FNA/CNB. Diagn. Cytopathol. 2016;44:351–360. © 2016 Wiley Periodicals, Inc.